Preparation method and application of low-formaldehyde high-toughness high-temperature-resistant amino resin
By preparing the blending of low-aldehyde high-toughness amino resin with silicone modified polyvinyl alcohol and composite nano silica, the hydrophobicity, stability and flammability of impregnated adhesive film paper is solved, and high water resistance and resistance are achieved Immersed adhesive film paper with combustion and wear resistance enhances its application value.
Patent Information
- Application Number
- CN202411103121.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-13
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-13
AI Technical Summary
The existing impregnated adhesive film paper has problems such as poor hydrophobic properties, high brittleness, poor storage stability, and flammability. The dehyde-free impregnated adhesive film paper has poor bonding strength and insufficient surface physical and chemical energy, which limits its application scope.
The preparation method of low-aldehyde, high-toughness, high-temperature resistant amino resin is prepared by mixing deionized water and formaldehyde, adding melamine and additives, and blending it with silicone modified polyvinyl alcohol and composite nanosilica to form a composite Impregnation liquid and coating liquid are used to prepare impregnated adhesive film paper to form layer-by-layer reinforcement protective films to improve their water resistance, flame retardancy and wear resistance.
Prepare green and environmentally friendly, good water resistance, high flame retardancy and good wear resistance, which improves its flexibility and service life and solves the hydrophobicity, stability and flammability of traditional impregnated adhesive paper. question.
Abstract
Description
Technical Field
[0001] The invention relates to the field of impregnated adhesive film paper, and in particular to a preparation method and application of a low-aldehyde, high-toughness, and high-temperature-resistant amino resin. Background Art
[0002] Impregnated film paper mostly refers to special paper impregnated in amino resin or phenolic resin. It is a commonly used finishing material for furniture and home decoration materials. In the production process of impregnated film paper, melamine formaldehyde resin impregnated film paper has developed rapidly because of the colorless and transparent resin used and high bonding strength. However, it still has disadvantages such as poor hydrophobicity, high brittleness and poor storage stability. Most of the formaldehyde-free impregnated film papers on the market have problems such as poor bonding strength and insufficient surface physical and chemical energy.
[0003] At the same time, as a surface decoration material, impregnated film paper is flammable, which limits its application scope to a certain extent. In order to strengthen environmental protection and improve the safety of materials, the development of an impregnated film paper with low formaldehyde, good water resistance, flame retardancy and wear resistance has great economic value and practical significance. Summary of the invention
[0004] The purpose of the present invention is to provide a preparation method and application of a low-aldehyde, high-toughness, high-temperature-resistant amino resin to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a low-aldehyde, high-toughness, high-temperature-resistant amino resin comprises the following steps:
[0007] Mix deionized water and formaldehyde, heat up to 60-65°C, add melamine, keep the pH at 8.9-9.1, heat up to 90°C, add additives, keep warm at 95-98°C for 1-2h, add auxiliary agents, keep warm at 82-87°C for 10-20min, cool down to 58-62°C, add solvent, cool down to 28-32°C, discharge, and obtain a low-aldehyde, high-toughness, high-temperature resistant amino resin.
[0008] Furthermore, the additive is one or more of p-toluenesulfonamide, methylguanamine, and caprolactam; the auxiliary agent is one or more of 1,4-butanediol, diethylene glycol, dipropylene glycol, and polyethylene glycol.
[0009] Furthermore, the solvent is one or a combination of ethanol, methanol and isopropanol.
[0010] Furthermore, the raw material composition of the amino resin is, by weight: 90-95 parts of deionized water, 50-60 parts of formaldehyde, 58-65 parts of melamine, 18-20 parts of additives, 4-4.5 parts of auxiliaries, and 1.5-2 parts of solvents.
[0011] Furthermore, an application of a low-formaldehyde, high-toughness, high-temperature-resistant amino resin is used to prepare impregnated film paper, and the preparation of the impregnated film paper includes the following steps:
[0012] S1: amino resin and silicone-modified polyvinyl alcohol are mixed in a mass ratio of 4:1 to form a composite impregnation liquid;
[0013] S2: putting the base paper into the composite impregnation liquid for impregnation treatment, and drying to obtain the pre-treated adhesive paper;
[0014] S3: mixing organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide to obtain a coating liquid;
[0015] S4: coating the coating liquid on the pre-treated adhesive paper, and drying to obtain an impregnated adhesive film paper.
[0016] Furthermore, the process conditions of the impregnation treatment are: time 35-45s, impregnation amount 88-98g / m 2 ; The coating process conditions are: coating amount is 103-113g / m 2 .
[0017] Furthermore, the mass ratio of organosilicon-modified polyvinyl alcohol to composite nano-silicon dioxide is 21:(2-5).
[0018] Further, the preparation of organosilicon-modified polyvinyl alcohol comprises the following steps:
[0019] Mix polyethylene glycol and deionized water, heat to 85-95°C and keep warm for 1-2 hours, cool to 55-65°C, add epoxy polymer containing double bonds and 3-glyceropropyltrimethoxysilane, adjust the pH of the solution to 7-8, keep warm for 2-3 hours, and obtain silicone-modified polyvinyl alcohol.
[0020] Further, the preparation of composite nano-silicon dioxide comprises the following steps:
[0021] 1) mixing n-butanol and nano-silica, ultrasonically vibrating for 10-15 minutes, heating to 78-82° C., adding vinyl polydimethylsiloxane, keeping the temperature for 4-6 hours, centrifuging, washing, drying, and grinding to obtain modified nano-silica;
[0022] 2) Under a nitrogen atmosphere, the modified nano-silica, dimethylaminoethyl methacrylate, and an epoxy polymer containing a double bond are mixed, and a mixed solution of azobisisobutyronitrile, dichloromethane, and methanol is added, and the temperature is raised to 65-75° C. and kept warm for 22-24 hours, and dichloromethane is added, and then centrifuged with petroleum ether, and dichloromethane and n-hexane are added in sequence, and the mixture is centrifuged, filtered, washed, and freeze-dried to obtain composite nano-silica.
[0023] Further, the preparation of the epoxy polymer containing double bonds comprises the following steps:
[0024] (1) Under a nitrogen atmosphere, magnolol, epichlorohydrin, and benzyltriethylammonium chloride are mixed, ultrasonically vibrated for 1-2 hours, heated to 83-87° C. and kept warm for 3-4 hours, cooled to 18-25° C., sodium hydroxide solution is added, kept warm for 1-2 hours, extracted with ethyl acetate, washed with saturated sodium chloride solution for 3-5 times, and dried to obtain a magnolol-based epoxy monomer containing a double bond;
[0025] (2) Under a nitrogen atmosphere, DOPO, p-hydroxybenzaldehyde and toluene are mixed, heated to 108-112° C. and kept warm for 1-2 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried under reduced pressure to obtain a flame retardant intermediate containing a hydroxyl group;
[0026] (3) heating the magnolia phenol-based epoxy monomer containing a double bond to 128-132° C., adding a flame retardant intermediate containing a hydroxyl group and butyl triphenylphosphonium bromide, keeping the temperature for 3-4 hours, cooling to 18-25° C., adding dichloromethane, washing with deionized water for 3-5 times, and drying to obtain an epoxy polymer containing a double bond.
[0027] Beneficial effects of the present invention:
[0028] The present invention provides a preparation method and application of a low-aldehyde, high-toughness, high-temperature-resistant amino resin. The prepared amino resin is low in aldehyde, high in toughness, and has good high-temperature resistance. The amino resin is used together with silicone-modified polyvinyl alcohol and composite nano-silicon dioxide as raw materials to prepare impregnated film paper, thereby obtaining green, environmentally friendly, water-resistant, highly flame-retardant, and wear-resistant impregnated film paper.
[0029] The present invention adopts process and component design, uses formaldehyde and melamine as raw materials, uses one or more of p-toluenesulfonamide, methylguanamine and caprolactam as additives, and uses one of 1,4-butanediol, diethylene glycol, dipropylene glycol and polyethylene glycol as an auxiliary agent to prepare low-aldehyde, high-toughness and high-temperature resistant amino resin; in order to improve the shortcomings of hydrophobicity, limited stability and low free formaldehyde content that still exist in the preparation of impregnated film paper using only amino resin as raw material, the present invention adopts amino resin and organosilicon-modified polyvinyl alcohol as impregnation stock solution, and uses organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide as coating solution to form layers of reinforced protective films on the surface of base paper, so as to prepare environmentally friendly impregnated film paper, which has excellent water resistance, flame retardancy and wear resistance.
[0030] In order to improve the flexibility, water resistance and flame retardancy of the impregnated film paper and enhance the utilization value of the amino resin, polyvinyl alcohol is grafted with an epoxy polymer containing double bonds and 3-glyceropropyltrimethoxysilane to obtain organosilicon-modified polyvinyl alcohol, which is blended with the amino resin to construct a complex cross-linking network, thereby improving the wettability of the composite impregnation liquid and improving the bonding strength with the base paper; at the same time, Si-O bonds are introduced to effectively improve the flexibility of the impregnated film paper; the epoxy polymer containing double bonds is prepared from magnolol, a biomass raw material containing rigid biphenyl structure, allyl group and phenolic hydroxyl group in the molecular structure, and is prepared with epichlorohydrin and benzyltriethylammonium chloride to prepare magnolol-based epoxy monomer containing double bonds, and then epoxy-hydroxyl ring opening is used to graft a high-efficiency phosphorus flame retardant DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and p-hydroxybenzaldehyde to prepare a flame retardant intermediate containing hydroxyl groups, thereby greatly improving its flame retardancy and thermal stability.
[0031] In order to further improve the hydrophobicity, wear resistance and flame retardancy of the impregnated film paper, nano silicon dioxide is introduced as a filler in the coating liquid. In order to improve the uniformity of the dispersion of nano silicon dioxide in the coating liquid, the nano silicon dioxide is modified by using vinyl polydimethylsiloxane to obtain hydrophobic modified nano silicon dioxide. In order to improve the bonding strength between the modified nano silicon dioxide and the organosilicon-modified polyvinyl alcohol and prevent the modified nano silicon dioxide from falling off from the coating layer formed by the coating liquid, modified nano silicon dioxide, dimethylaminoethyl methacrylate and epoxy polymer containing double bonds are used as raw materials. Under the action of the initiator azobisisobutyronitrile, free radical polymerization is used to obtain composite nano silicon dioxide with multiple active sites, thereby improving its compatibility with the organosilicon-modified polyvinyl alcohol, giving the impregnated film paper long-lasting excellent water resistance, flame retardancy and wear resistance, thereby improving the service life of the impregnated film paper. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0034] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0035] Example 1: Application of a low-formaldehyde, high-toughness, high-temperature-resistant amino resin for the preparation of impregnated film paper, the preparation of the impregnated film paper comprising the following steps:
[0036] S1: amino resin and silicone-modified polyvinyl alcohol are mixed in a mass ratio of 4:1 to form a composite impregnation liquid;
[0037] The preparation method of amino resin comprises the following steps:
[0038] Deionized water and formaldehyde are mixed, heated to 60°C, melamine is added, the pH is kept at 8.9, heated to 90°C, additives are added, the temperature is kept at 95°C for 2h, auxiliary agents are added, the temperature is kept at 82°C for 20min, the temperature is lowered to 58°C, solvent is added, the temperature is lowered to 28°C, and the material is discharged to obtain a low-aldehyde, high-toughness, high-temperature-resistant amino resin;
[0039] The additive is methylguanamine; the auxiliary agent is 1,4-butanediol; the solvent is ethanol; the raw material composition of the amino resin is: 90 parts of deionized water, 50 parts of formaldehyde, 58 parts of melamine, 18 parts of additives, 4 parts of auxiliary agents, and 1.5 parts of solvents in parts by mass;
[0040] The preparation of the organosilicon-modified polyvinyl alcohol comprises the following steps:
[0041] 1 g of polyethylene glycol and 99 mL of deionized water were mixed, the temperature was raised to 85° C. and kept for 2 h, the temperature was lowered to 55° C., 5 g of epoxy polymer containing double bonds and 3 g of 3-glyceropropyltrimethoxysilane were added, the pH of the solution was adjusted to 7, and the temperature was kept for 2 h to obtain silicone-modified polyvinyl alcohol;
[0042] The preparation of the epoxy polymer containing double bonds comprises the following steps:
[0043] (1) Under a nitrogen atmosphere, 8.1 g of magnolol, 2.83 g of epichlorohydrin, and 0.5 g of benzyltriethylammonium chloride were mixed, ultrasonically oscillated for 1 h, heated to 83° C. and kept warm for 4 h, cooled to 18° C., 100 mL of a 40% sodium hydroxide solution was added, kept warm for 1 h, extracted with ethyl acetate, washed three times with a saturated sodium chloride solution, and dried to obtain a magnolol-based epoxy monomer containing a double bond;
[0044] (2) Under a nitrogen atmosphere, 11.9 g DOPO, 6.1 g p-hydroxybenzaldehyde, and 150 mL toluene were mixed, heated to 108° C. and kept warm for 2 h, filtered, washed with anhydrous ethanol three times, and dried under reduced pressure to obtain a flame retardant intermediate containing hydroxyl groups;
[0045] (3) heating 25 g of magnolia phenol-based epoxy monomer containing double bonds to 128° C., adding 12 g of a flame retardant intermediate containing a hydroxyl group and 0.25 g of butyltriphenylphosphonium bromide, keeping the temperature for 3 h, cooling to 18° C., adding 100 mL of dichloromethane, washing with deionized water for 3 times, and drying to obtain an epoxy polymer containing double bonds;
[0046] S2: putting the base paper into the composite impregnation liquid for impregnation treatment, and drying to obtain the pre-treated adhesive paper;
[0047] The process conditions of the impregnation treatment are: temperature 40°C, time 45s, impregnation amount 92g / m 2 ;
[0048] S3: mixing organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide to obtain a coating liquid;
[0049] The mass ratio of organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide is 21:2;
[0050] The preparation of the composite nano-silicon dioxide comprises the following steps:
[0051] 1) 100 g of n-butanol and 5 g of nano-silica were mixed, ultrasonically vibrated for 10 min, heated to 78° C., vinyl polydimethylsiloxane was added, and the mixture was kept warm for 4 h. The mixture was centrifuged, washed, dried, and ground to obtain modified nano-silica;
[0052] 2) Under a nitrogen atmosphere, 5 g of modified nano-silica, 4 g of dimethylaminoethyl methacrylate, and 10 g of an epoxy polymer containing a double bond were mixed, 0.1 g of azobisisobutyronitrile, 40 mL of dichloromethane, and 40 mL of a methanol mixture were added, the mixture was heated to 65° C. and kept warm for 24 h, 80 mL of dichloromethane was added, and then centrifuged with petroleum ether, 80 mL of dichloromethane was added, 60 mL of n-hexane was added, centrifuged, filtered, washed, and freeze-dried to obtain composite nano-silica;
[0053] The coating process conditions are: coating amount is 103g / m 2 ;
[0054] S4: coating the coating liquid on the pre-treated adhesive paper, and drying to obtain an impregnated adhesive film paper.
[0055] Example 2: Application of a low-formaldehyde, high-toughness, high-temperature-resistant amino resin for the preparation of impregnated film paper, the preparation of the impregnated film paper comprising the following steps:
[0056] S1: amino resin and silicone-modified polyvinyl alcohol are mixed in a mass ratio of 4:1 to form a composite impregnation liquid;
[0057] The preparation method of amino resin comprises the following steps:
[0058] Deionized water and formaldehyde are mixed, heated to 63°C, melamine is added, the pH is maintained at 9, the temperature is raised to 90°C, additives are added, the temperature is kept at 96°C for 1.5 hours, auxiliary agents are added, the temperature is kept at 85°C for 15 minutes, the temperature is lowered to 60°C, solvents are added, the temperature is lowered to 30°C, and the material is discharged to obtain a low-aldehyde, high-toughness, high-temperature-resistant amino resin;
[0059] The additive is methylguanamine; the auxiliary agent is 1,4-butanediol; the solvent is ethanol; the raw material composition of the amino resin is: 93 parts of deionized water, 55 parts of formaldehyde, 62 parts of melamine, 19 parts of additives, 4.2 parts of auxiliary agents, and 1.8 parts of solvents in terms of mass fractions;
[0060] The preparation of the organosilicon-modified polyvinyl alcohol comprises the following steps:
[0061] 1 g of polyethylene glycol and 99 mL of deionized water were mixed, the temperature was raised to 90° C. and kept for 1.5 h, the temperature was lowered to 60° C., 5 g of epoxy polymer containing double bonds and 3 g of 3-glyceropropyltrimethoxysilane were added, the pH of the solution was adjusted to 7.5, and the temperature was kept for 2.5 h to obtain organosilicon-modified polyvinyl alcohol;
[0062] The preparation of the epoxy polymer containing double bonds comprises the following steps:
[0063] (1) Under a nitrogen atmosphere, 8.1 g of magnolol, 2.83 g of epichlorohydrin, and 0.5 g of benzyltriethylammonium chloride were mixed, ultrasonically oscillated for 1.5 h, heated to 85° C. and kept warm for 3.5 h, cooled to 20° C., 100 mL of 40% sodium hydroxide solution was added, kept warm for 1.5 h, extracted with ethyl acetate, washed with saturated sodium chloride solution 4 times, and dried to obtain a magnolol-based epoxy monomer containing a double bond;
[0064] (2) Under a nitrogen atmosphere, 11.9 g DOPO, 6.1 g p-hydroxybenzaldehyde, and 150 mL toluene were mixed, heated to 110° C. and kept warm for 1.5 h, filtered, washed with anhydrous ethanol 4 times, and dried under reduced pressure to obtain a flame retardant intermediate containing a hydroxyl group;
[0065] (3) heating 25 g of a magnolia phenol-based epoxy monomer containing a double bond to 130° C., adding 12 g of a flame retardant intermediate containing a hydroxyl group and 0.25 g of butyltriphenylphosphonium bromide, keeping the temperature for 3.5 h, cooling to 20° C., adding 100 mL of dichloromethane, washing with deionized water 4 times, and drying to obtain an epoxy polymer containing a double bond;
[0066] S2: putting the base paper into the composite impregnation liquid for impregnation treatment, and drying to obtain the pre-treated adhesive paper;
[0067] The process conditions of the impregnation treatment are: temperature 45°C, time 40s, impregnation amount 92g / m 2 ;
[0068] S3: mixing organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide to obtain a coating liquid;
[0069] The mass ratio of organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide is 21:3;
[0070] The preparation of the composite nano-silicon dioxide comprises the following steps:
[0071] 1) 100 g of n-butanol and 5 g of nano-silica were mixed, ultrasonically vibrated for 12 min, heated to 80° C., vinyl polydimethylsiloxane was added, and the mixture was kept warm for 5 h. The mixture was centrifuged, washed, dried, and ground to obtain modified nano-silica;
[0072] 2) Under a nitrogen atmosphere, 5 g of modified nano-silica, 4 g of dimethylaminoethyl methacrylate, and 10 g of an epoxy polymer containing a double bond were mixed, 0.1 g of azobisisobutyronitrile, 40 mL of dichloromethane, and 40 mL of a methanol mixture were added, the mixture was heated to 70° C. and kept warm for 23 h, 80 mL of dichloromethane was added, and then centrifuged with petroleum ether, 80 mL of dichloromethane was added, 60 mL of n-hexane was added, centrifuged, filtered, washed, and freeze-dried to obtain composite nano-silica;
[0073] The coating process conditions are: coating amount is 109g / m 2 ;
[0074] S4: coating the coating liquid on the pre-treated adhesive paper, and drying to obtain an impregnated adhesive film paper.
[0075] Example 3: Application of a low-formaldehyde, high-toughness, high-temperature-resistant amino resin for the preparation of impregnated film paper, the preparation of the impregnated film paper comprising the following steps:
[0076] S1: amino resin and silicone-modified polyvinyl alcohol are mixed in a mass ratio of 4:1 to form a composite impregnation liquid;
[0077] The preparation method of amino resin comprises the following steps:
[0078] Deionized water and formaldehyde are mixed, heated to 65°C, melamine is added, the pH is maintained at 9.1, the temperature is raised to 90°C, additives are added, the temperature is kept at 98°C for 1 hour, auxiliary agents are added, the temperature is kept at 87°C for 10 minutes, the temperature is lowered to 58°C, solvents are added, the temperature is lowered to 32°C, and the material is discharged to obtain a low-aldehyde, high-toughness, high-temperature-resistant amino resin;
[0079] The additive is methylguanamine; the auxiliary agent is 1,4-butanediol; the solvent is ethanol; the raw material composition of the amino resin is: 95 parts of deionized water, 60 parts of formaldehyde, 65 parts of melamine, 20 parts of additives, 4.5 parts of auxiliary agents, and 2 parts of solvents in terms of mass parts;
[0080] The preparation of the organosilicon-modified polyvinyl alcohol comprises the following steps:
[0081] 1 g of polyethylene glycol and 99 mL of deionized water were mixed, the temperature was raised to 95° C. and kept for 1 h, the temperature was lowered to 65° C., 5 g of epoxy polymer containing double bonds and 3 g of 3-glyceropropyltrimethoxysilane were added, the pH of the solution was adjusted to 8, and the temperature was kept for 3 h to obtain silicone-modified polyvinyl alcohol;
[0082] The preparation of the epoxy polymer containing double bonds comprises the following steps:
[0083] (1) Under a nitrogen atmosphere, 8.1 g of magnolol, 2.83 g of epichlorohydrin, and 0.5 g of benzyltriethylammonium chloride were mixed, ultrasonically oscillated for 2 h, heated to 87° C. and kept warm for 3 h, cooled to 25° C., 100 mL of a 40% sodium hydroxide solution was added, kept warm for 2 h, extracted with ethyl acetate, washed with a saturated sodium chloride solution 5 times, and dried to obtain a magnolol-based epoxy monomer containing a double bond;
[0084] (2) Under a nitrogen atmosphere, 11.9 g of DOPO, 6.1 g of p-hydroxybenzaldehyde, and 150 mL of toluene were mixed, heated to 112° C. and kept warm for 1 h, filtered, washed with anhydrous ethanol 5 times, and dried under reduced pressure to obtain a flame retardant intermediate containing a hydroxyl group;
[0085] (3) heating 25 g of a magnolol-based epoxy monomer containing a double bond to 132° C., adding 12 g of a flame retardant intermediate containing a hydroxyl group and 0.25 g of butyltriphenylphosphonium bromide, keeping the temperature for 4 h, cooling to 25° C., adding 100 mL of dichloromethane, washing with deionized water 5 times, and drying to obtain an epoxy polymer containing a double bond;
[0086] S2: putting the base paper into the composite impregnation liquid for impregnation treatment, and drying to obtain the pre-treated adhesive paper;
[0087] The process conditions of the impregnation treatment are: temperature 50°C, time 35s, impregnation amount 92g / m 2 ;
[0088] S3: mixing organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide to obtain a coating liquid;
[0089] The mass ratio of organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide is 21:5;
[0090] The preparation of the composite nano-silicon dioxide comprises the following steps:
[0091] 1) 100 g of n-butanol and 5 g of nano-silica were mixed, ultrasonically vibrated for 15 min, heated to 82° C., vinyl polydimethylsiloxane was added, and the mixture was kept warm for 6 h. The mixture was centrifuged, washed, dried, and ground to obtain modified nano-silica;
[0092] 2) Under a nitrogen atmosphere, 5 g of modified nano-silica, 4 g of dimethylaminoethyl methacrylate, and 10 g of an epoxy polymer containing a double bond were mixed, 0.1 g of azobisisobutyronitrile, 40 mL of dichloromethane, and 40 mL of a methanol mixture were added, the mixture was heated to 75° C. and kept warm for 22 h, 80 mL of dichloromethane was added, and then centrifuged with petroleum ether, 80 mL of dichloromethane was added, 60 mL of n-hexane was added, centrifuged, filtered, washed, and freeze-dried to obtain composite nano-silica;
[0093] The coating process conditions are: coating amount is 113g / m 2 ;
[0094] S4: coating the coating liquid on the pre-treated adhesive paper, and drying to obtain an impregnated adhesive film paper.
[0095] Comparative Example 1: Taking Example 3 as the control group, nano silicon dioxide was used to replace the composite nano silicon dioxide, and the other processes were normal.
[0096] Comparative Example 2: Taking Example 3 as the control group, polyvinyl alcohol was used to replace the silicone-modified polyvinyl alcohol, and the other processes were normal.
[0097] Comparative Example 3: Example 3 was used as a control group, in which no epoxy polymer containing double bonds was prepared, and other processes were normal.
[0098] Source of raw materials (for demonstration only):
[0099] Base paper (recycled kraft paper, thickness 0.2 mm): Chengdu Zhuyuansheng Paper Co., Ltd.; melamine 1: Shandong Xinheng Chemical Co., Ltd.; vinyl polydimethylsiloxane 53529-60-5: Hubei Jusheng Technology Co., Ltd.; methylguanamine A106445, 1,4-butanediol B110391, polyethylene glycol P103719, 3-glyceropropyltrimethoxysilane G107576, magnolol M111378, epichlorohydrin E1081 82. Benzyltriethylammonium chloride B108417, DOPOD102416, p-hydroxybenzaldehyde H100420, butyltriphenylphosphonium bromide B107826, nano-silica S104596, dimethylaminoethyl methacrylate D111129, azobisisobutyronitrile A434183: Aladdin reagent; formic acid, ethanol, sodium hydroxide, ethyl acetate, sodium chloride, toluene, dichloromethane, n-butanol, n-hexane, analytical grade: Sinopharm reagent.
[0100] Performance test: The impregnated film paper prepared in the embodiment and comparative example was tested:
[0101] Flame retardancy: UL-94 vertical burning rating test was conducted; Hydrophobicity: tested using a contact angle tester with a 4 μL deionized water droplet; Abrasion resistance: The sample was placed on 200-grit sandpaper and pressed with a 10g weight, pulled at a speed of 2mm / min, with a distance of 10cm as a cycle, and the water contact angle was tested after 20 cycles, and the change rate was characterized compared with the initial contact angle. If it is less than 2% (including 2%), it is excellent, otherwise it is unqualified; the results are shown in Table 1 below;
[0102] Table 1
[0103] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Flame retardant grade V-0 V-0 V-0 V-1 V-1 V-2 Water contact angle (°) 132.8 132.9 133.1 126.2 128.7 121.5 Wear resistance excellent excellent excellent Failure Failure Failure
[0104] The present invention provides a preparation method and application of a low-aldehyde, high-toughness, high-temperature-resistant amino resin. The prepared amino resin is low in aldehyde, high in toughness, and has good high-temperature resistance. The amino resin is used together with silicone-modified polyvinyl alcohol and composite nano-silicon dioxide as raw materials to prepare impregnated film paper, thereby obtaining green, environmentally friendly, water-resistant, highly flame-retardant, and wear-resistant impregnated film paper.
[0105] Example 3 is compared with Comparative Examples 1 and 3. In order to further improve the hydrophobicity, wear resistance and flame retardancy of the impregnated film paper, nano silicon dioxide is introduced as a coating liquid filler. In order to improve the uniformity of the dispersion of nano silicon dioxide in the coating liquid, the nano silicon dioxide is modified by using vinyl polydimethylsiloxane to obtain hydrophobic modified nano silicon dioxide. In order to improve the bonding strength between the modified nano silicon dioxide and the organosilicon-modified polyvinyl alcohol and prevent the modified nano silicon dioxide from falling off from the coating layer formed by the coating liquid, vinyl-modified nano silicon dioxide, dimethylaminoethyl methacrylate and epoxy polymer containing double bonds are used as raw materials. Under the action of the initiator azobisisobutyronitrile, free radical polymerization is used to obtain composite nano silicon dioxide with multiple active sites, thereby improving its compatibility with the organosilicon-modified polyvinyl alcohol, giving the impregnated film paper long-lasting excellent water resistance, flame retardancy and wear resistance, thereby improving the service life of the impregnated film paper.
[0106] Example 3 is compared with Comparative Examples 2 and 3. In order to improve the flexibility, water resistance and flame retardancy of the impregnated film paper and enhance the utilization value of the amino resin, polyvinyl alcohol is grafted with an epoxy polymer containing a double bond and 3-glycerylpropyltrimethoxysilane to obtain organosilicon-modified polyvinyl alcohol, which is blended with the amino resin to construct a complex cross-linked network, thereby improving the wettability of the composite impregnation liquid and the bonding strength with the base paper; at the same time, Si-O bonds are introduced to effectively enhance the flexibility of the impregnated film paper. The epoxy polymer containing double bonds is prepared from magnolia phenol, a biomass raw material containing a rigid biphenyl structure, an allyl group, and a phenolic hydroxyl group in its molecular structure, and is reacted with epichlorohydrin and benzyltriethylammonium chloride to prepare a magnolia phenol-based epoxy monomer containing double bonds. The epoxy-hydroxyl ring is then opened and grafted with a high-efficiency phosphorus-based flame retardant DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) and p-hydroxybenzaldehyde to prepare a flame retardant intermediate containing hydroxyl groups, thereby greatly improving its flame retardancy and thermal stability.
[0107] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a low-aldehyde, high-toughness, high-temperature-resistant amino resin. It is characterized in that The following steps are involved: Mix deionized water and formaldehyde, heat up to 60-65°C, add melamine, keep the pH at 8.9-9.1, heat up to 90°C, add additives, keep warm at 95-98°C for 1-2h, add auxiliary agents, keep warm at 82-87°C for 10-20min, cool down to 58-62°C, add solvent, cool down to 28-32°C, discharge, and obtain a low-aldehyde, high-toughness, high-temperature resistant amino resin.
2. The method for preparing a low-aldehyde, high-toughness, high-temperature-resistant amino resin according to claim 1, It is characterized in that The additive is one or a combination of p-toluenesulfonamide, methylguanamine and caprolactam; the auxiliary agent is one or a combination of 1,4-butanediol, diethylene glycol, dipropylene glycol and polyethylene glycol.
3. The method for preparing a low-aldehyde, high-toughness, high-temperature-resistant amino resin according to claim 1, It is characterized in that The solvent is one or a combination of ethanol, methanol and isopropanol.
4. The method for preparing a low-aldehyde, high-toughness, high-temperature-resistant amino resin according to claim 1, It is characterized in that The raw material composition of the amino resin is as follows, by weight: 90-95 parts of deionized water, 50-60 parts of formaldehyde, 58-65 parts of melamine, 18-20 parts of additives, 4-4.5 parts of auxiliary agents, and 1.5-2 parts of solvents.
5. Application of a low-aldehyde, high-toughness, high-temperature-resistant amino resin, It is characterized in that The amino resin prepared by the preparation method according to any one of claims 1 to 4 is used to prepare impregnated film paper, and the preparation of the impregnated film paper comprises the following steps: S1: amino resin and silicone-modified polyvinyl alcohol are mixed in a mass ratio of 4:1 to form a composite impregnation liquid; S2: putting the base paper into the composite impregnation liquid for impregnation treatment, and drying to obtain the pre-treated adhesive paper; S3: mixing organosilicon-modified polyvinyl alcohol and composite nano-silicon dioxide to obtain a coating liquid; S4: coating the coating liquid on the pre-treated adhesive paper, and drying to obtain an impregnated adhesive film paper.
6. Application of a low-aldehyde, high-toughness, high-temperature-resistant amino resin according to claim 5, It is characterized in that The process conditions of the impregnation treatment are: temperature 40-50℃, time 35-45s, impregnation amount 88-98g / m 2 ; The coating process conditions are: coating amount is 103-113g / m 2 .
7. Application of a low-formaldehyde, high-toughness, high-temperature-resistant amino resin according to claim 5, It is characterized in that The mass ratio of organosilicon-modified polyvinyl alcohol to composite nano-silicon dioxide is 21:(2-5).
8. Application of a low-aldehyde, high-toughness, high-temperature-resistant amino resin according to claim 5, It is characterized in that The preparation of the organosilicon-modified polyvinyl alcohol comprises the following steps: Mix polyethylene glycol and deionized water, heat to 85-95°C and keep warm for 1-2 hours, cool to 55-65°C, add epoxy polymer containing double bonds and 3-glyceropropyltrimethoxysilane, adjust the pH of the solution to 7-8, keep warm for 2-3 hours, and obtain silicone-modified polyvinyl alcohol.
9. Application of a low-formaldehyde, high-toughness, high-temperature-resistant amino resin according to claim 5, It is characterized in that The preparation of the composite nano-silicon dioxide comprises the following steps: 1) mixing n-butanol and nano-silica, ultrasonically vibrating for 10-15 minutes, heating to 78-82° C., adding vinyl polydimethylsiloxane, keeping the temperature for 4-6 hours, centrifuging, washing, drying, and grinding to obtain modified nano-silica; 2) Under a nitrogen atmosphere, the modified nano-silica, dimethylaminoethyl methacrylate, and an epoxy polymer containing a double bond are mixed, and a mixed solution of azobisisobutyronitrile, dichloromethane, and methanol is added, and the temperature is raised to 65-75° C. and kept warm for 22-24 hours, and dichloromethane is added, and then centrifuged with petroleum ether, and dichloromethane and n-hexane are added in sequence, and the mixture is centrifuged, filtered, washed, and freeze-dried to obtain composite nano-silica.
10. Use of a low-aldehyde, high-toughness, high-temperature-resistant amino resin according to claim 8 or 9, It is characterized in that The preparation of the epoxy polymer containing double bonds comprises the following steps: (1) Under a nitrogen atmosphere, magnolol, epichlorohydrin, and benzyltriethylammonium chloride are mixed, ultrasonically vibrated for 1-2 hours, heated to 83-87° C. and kept warm for 3-4 hours, cooled to 18-25° C., sodium hydroxide solution is added, kept warm for 1-2 hours, extracted with ethyl acetate, washed with saturated sodium chloride solution for 3-5 times, and dried to obtain a magnolol-based epoxy monomer containing a double bond; (2) Under a nitrogen atmosphere, DOPO, p-hydroxybenzaldehyde and toluene are mixed, heated to 108-112° C. and kept warm for 1-2 hours, filtered, washed with anhydrous ethanol for 3-5 times, and dried under reduced pressure to obtain a flame retardant intermediate containing a hydroxyl group; (3) heating the magnolia phenol-based epoxy monomer containing a double bond to 128-132° C., adding a flame retardant intermediate containing a hydroxyl group and butyl triphenylphosphonium bromide, keeping the temperature for 3-4 hours, cooling to 18-25° C., adding dichloromethane, washing with deionized water for 3-5 times, and drying to obtain an epoxy polymer containing a double bond.
Citation Information
Patent Citations
High-brightness wear-resistant decorative sticky membrane paper and preparation method thereof
CN103147346A
Low-formaldehyde adhesive film paper for wardrobe
CN109235135A
Door plate and production process thereof
CN115157405A
Anti-fingerprint skin feeling matte melamine veneer and manufacturing method thereof
CN116117943A
Waterdilutable, etherified melamine-formaldehyde resins
EP1266917A1
Cited By
PLA composite material for 3D printing and preparation method thereof
CN120682617A
PLA composite material for 3D printing and preparation method thereof
CN120682617B
